Complete characterization of single-cycle double ionization of argon from the nonsequential to the sequential ionization regime - Kubel, M.; Burger, C.; Kling, Nora G.; Pischke, T.; Beaufore, L.; Ben-Itzhak, Itzhak; Paulus, G. G.; Ullrich, J.; Pfeifer, T.; Moshammer, R.; Kling, Matthias F.; Bergues, B. (My University, 2016)
Selected features of nonsequential double ionization have been qualitatively reproduced by a multitude of different (quantum and classical) approaches. In general, however, the typical uncertainty of laser pulse parameters and the restricted number of observables measured in individual experiments leave room for adjusting theoretical results to match the experimental data. While this has been hampering the assessment of different theoretical approaches leading to conflicting interpretations, comprehensive experimental data that would allow such an ultimate and quantitative assessment have been missing so far. To remedy this situation we have performed a kinematically complete measurement of single-cycle multiple ionization of argon over a one order of magnitude range of intensity. The momenta of electrons and ions resulting from the ionization of the target gas are measured in coincidence, while each ionization event is tagged with the carrier-envelope phase and intensity of the 4-fs laser pulse driving the process. The acquired highly differential experimental data provide a benchmark for a rigorous test of the many competing theoretical models used to describe nonsequential double ionization.
Citation: Kubel, M., Burger, C., Kling, N. G., Pischke, T., Beaufore, L., Ben-Itzhak, I., . . . Bergues, B. (2016). Complete characterization of single-cycle double ionization of argon from the nonsequential to the sequential ionization regime. Physical Review A, 93(5), 9. doi:10.1103/PhysRevA.93.053422
Keywords: Correlated Electron-Emission; Multiple Ionization; Field; Atoms; Pulses; Lasers